Trans-Border Land Migration and Crime in The Nigeria-Niger Border (2015-2023) - Haruna, Naziru (Journal of Contemporary International Relations and Diplomacy, 2024)
The porous nature of the Nigeria-Niger border has, over the years, fueled illegal migration. This has been discovered to be among the factors responsible for the persistence of border crimes and, which, has posed a serious challenge to border security for the two countries. This paper examined the porosity of the border and shortage of manpower as responsible for the illegal land migration. The study analysis trans-border land migration and crime, within the framework of Securitization theory which believes that the ideas of security should not be limited to military or political aspect of threat alone, but also issues which affect regional and human security. The study used secondary data and the content analysis of the information generated by exploring and examining published texts on the Nigeria-Niger land border migration, border security, border crimes, smuggling, etc. In this regards, the data were collected solely through documentation of secondary sources, including review of related literature, and newspapers. The study finds that the porous nature of the borders breed regional insecurity and human security threats, the persistence of terrorism, insurgency, armed banditry, armed robbery, theft, smuggling, among many other social and security challenges in the border areas. Furthermore, there is inadequate manpower to secure the Nigeria-Niger border, and the need for a modern technology that can simplify prompt security response by both countries. The paper recommends that both borders need to be manned by more manpower and modern technology for instant identification of illegal migrants along the route by both countries.